2015
DOI: 10.3109/10717544.2015.1049719
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured lipid carriers enhance the bioavailability and brain cancer inhibitory efficacy of curcumin both in vitro and in vivo

Abstract: Brain cancer is a kind of tough carcinoma because the blood-brain barrier (BBB) remains a formidable obstacle in medicine. Curcumin (Cur) was determined to have anticancer potency on several kinds of carcinoma. However, its medical application was limited because of its poor bioavailability, unsatisfying dispersity and rapid metabolism in vivo. In this study, Cur was delivered by nanostructured lipid carriers (NLCs) for brain cancer treatment. The physiochemical characters of NLC-Cur were detected by using hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 33 publications
(32 reference statements)
0
40
0
Order By: Relevance
“…This is due to breakage of the hydrogen bonds between the surfactant molecules at the lipid/water interface as a result of increasing temperature [73]. It was also noticed that the ZP of particles stored at 22 • C was decreased at longer storage duration, which is associated to agglomeration and aggregation of the particles [19].…”
Section: Stabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…This is due to breakage of the hydrogen bonds between the surfactant molecules at the lipid/water interface as a result of increasing temperature [73]. It was also noticed that the ZP of particles stored at 22 • C was decreased at longer storage duration, which is associated to agglomeration and aggregation of the particles [19].…”
Section: Stabilitymentioning
confidence: 97%
“…Glyceryl monostearate [9,[15][16][17] Glyceryl tridecanoate [18] Glyceryl tripalmitate [18,19] Glyceryl behenate (Compritol ® 888 ATO) [20][21][22][23] Stearic acid [16,24,25] Glyceryl distearate (Precirol ® ATO 5) [21,23,[26][27][28] Liquid lipids…”
Section: Solid Lipidsmentioning
confidence: 99%
“…Nanostructured lipid carriers (tripalmitin-oleic acid) loaded with curcumin had IC 50 of approximately 20  μ g/mL against A172 GBM cells compared to IC 50 of 80  μ g/mL with curcumin alone. Further, the authors showed that curcumin delivered with the lipid carriers to subcutaneous flank tumor bearing nude mice decreased tumor volume by 82% [74]. Polymeric micelles have also been studied for curcumin delivery.…”
Section: Delivery Mechanismsmentioning
confidence: 99%
“…Figure 5(f) showed that both CUR-NSps and injections group had obvious drug distribution in brain, which demonstrated that both CUR-NSps and injections group could pass through the blood brain barrier (BBB) into brain tissue. But CUR-NSps demonstrated a higher CUR concentration in brain at all time-points, which might be the result of transport of the CUR-NSps through the blood-brain barrier by endocytosis and sustained diffusion release of CUR from nanosuspensions (Minagawa et al, 1996;Tsai et al, 2011;Chen et al, 2016).…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%